2009
DOI: 10.1159/000228155
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Anthropometry and Motor Abilities at Pre-School Age

Abstract: Objective: Little is known to date about the relationship between poor motor abilities and overweight or obese pre-school children. Thus, this study examined the association between motor abilities and weight status in 1,228 kindergarten children (45.8% female). Method: Anthropometric data were assessed; age 4.7 ± 1.0 years; height 108.6 ± 8.0 cm; weight 19.1 ± 3.6 kg; BMI 16.1 ± 1.5 kg/m2. The modified Karlsruher Motor Ability Screening Test was carried out to determine the motor abilities of speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…However, these results were inconclusive, and differences between groups were generally based on BMI. Some of these studies showed that obese children were better in some tasks, such as throwing performance [40,41] and static balance [42]. Another study found a different impact of BMI on fine and gross motor skills [43]: only the gross motor skills were inversely related to BMI.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results were inconclusive, and differences between groups were generally based on BMI. Some of these studies showed that obese children were better in some tasks, such as throwing performance [40,41] and static balance [42]. Another study found a different impact of BMI on fine and gross motor skills [43]: only the gross motor skills were inversely related to BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has been linked to lower levels of fitness and motor skills in older children both cross-sectionally [3438] and longitudinally [31, 39]. Obesity in infancy may delay achievement of gross motor milestones [31, 39, 40] and conversely, infants who attain motor milestones at later ages may be less physically active later in childhood [31]. These infants may prevent development of excess adiposity by building more muscle mass, expending more calories, and improving cardiovascular function.…”
Section: Introductionmentioning
confidence: 99%
“…In a second pediatric study, de Toia (Germany) et al [2] examined the relationship between motor abilities and body weight in 1,228 kindergarten children. In school-aged overweight and obese children motor abilities have been shown to be reduced; however, little is known about preschoolers.…”
Section: On the Contents Of This Issuementioning
confidence: 99%
“…Depression is common in patients with diabetes mellitus [2]. The prevalence of any depression (major or minor forms) is significantly higher in patients with type 2 diabetes mellitus (T2DM) than in those without diabetes (17.6 vs. 9.8%) [3].…”
mentioning
confidence: 99%